Analisis Kesalahan Berbahasa Bidang Sintaksis Pada Rubrik “Keluarga” Surat Kabar Kedaulatan Rakyat Edisi 16 Februari 2020 - Muhammad Alfian Hermawan; Lilis Ferawati; Risma Citra (PIKTORIAL : Journal of Humanities, 2020)
This study aims to determine the mistakes in the Indonesian language in the field of syntax in the Kedaulatan Rakyat newspaper. The date source of this research is the family rubric in the Kedaulatan Rakyat newspaper, February 16, 2020 edition. In this study, the methods and data collection techniques use the note note method. The references used in this study are the Big Indonesian Dictionary online (KBBI), the Indonesian Spelling General Guidelines Acronym (PUEBI) and the opinions of experts conveyed through research relevant to this research. From the results of the analysis there were 9 syntactic language errors in the Kedaulatan Rakyat newspaper rubric of this family. Including 6 redundant words, 2 inappropriate word choice, and 1 anaphora (inaccurate cross-references). Keywords: Error, Language, Field, Syntactic, Newspaper